EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN AKTIF LEARNING TERHADAP HASIL BELAJAR MATEMATIKA DI SD NEGERI 018 RAMBAH SAMO - Alfaro, Fhardlon; Wahyudi, Sri; Chandra, Detri Amelia; Muslim, Muslim (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the effectiveness of the Active Learning model in improving mathematics learning outcomes among elementary school students. The research is motivated by the low levels of student participation and academic achievement, particularly in mathematics, which remains below the minimum competency threshold. A quantitative approach was employed using a pre-experimental design of the One-Group Pretest-Posttest Design type, involving 23 fourth-grade students at SD Negeri 018 Rambah Samo as research subjects. Data collection instruments included mathematics learning outcome tests, student activity observation sheets, and implementation observation sheets for the Active Learning model. The findings revealed that the average pre-test score was 61.087, which increased to 77.608 in the post-test. The calculated normalized gain (N-gain) score of 0.425 falls into the moderate category, indicating that the Active Learning model is fairly effective in enhancing students’ mathematics achievement. Moreover, the percentage of students achieving mastery rose from 17.39% to 65.22% after the implementation of the model. Observational data also indicated a significant increase in student engagement during lessons, and teachers were able to implement each stage of the learning model in a structured and consistent manner. Therefore, the Active Learning model is considered a viable instructional strategy to improve mathematics learning outcomes in elementary education. Keyword: Active Learning, Learning Outcomes, N-gain Abstrak: Penelitian ini bertujuan untuk menganalisis efektivitas model pembelajaran Active Learning dalam meningkatkan hasil belajar matematika siswa sekolah dasar. Latar belakang penelitian ini didasarkan pada rendahnya partisipasi aktif dan capaian belajar siswa yang masih di bawah standar ketuntasan minimal, khususnya pada mata pelajaran matematika. Penelitian menggunakan pendekatan kuantitatif dengan desain pre-eksperimen tipe One-Group Pretest-Posttest Design, melibatkan 23 siswa kelas IV SD Negeri 018 Rambah Samo sebagai subjek penelitian. Instrumen pengumpulan data meliputi tes hasil belajar matematika, lembar observasi keaktifan siswa, dan lembar observasi keterlaksanaan pembelajaran. Hasil penelitian menunjukkan bahwa rata-rata nilai pre-test siswa adalah 61,087 dan meningkat menjadi 77,608 pada post-test. Nilai normalized gain (N-gain) yang dihitung berdasarkan rerata skor sebesar 0,425 tergolong dalam kategori sedang, yang menunjukkan bahwa model Active Learning cukup efektif dalam meningkatkan hasil belajar matematika. Persentase ketuntasan siswa juga meningkat dari 17,39% menjadi 65,22% setelah diterapkannya model pembelajaran ini. Selain itu, hasil observasi menunjukkan bahwa siswa lebih aktif dalam proses pembelajaran dan guru mampu melaksanakan tahapan pembelajaran secara terstruktur. Dengan demikian, model pembelajaran Active Learning layak untuk diterapkan sebagai strategi alternatif dalam pembelajaran matematika di jenjang sekolah dasar. Kata kunci: Active Learning, hasil belajar, N-gain